Sports violence associated with football matches, a case study of Houari Abu Madian Stadium in Palestine - Case Study - Nassr, Salem Khalil (Journal of Humanities & Social Sciences, 2024)
The study aimed to identify the causes of sports violence in Palestinian stadiums and change strategies that could limit it in the foreseeable future, he studies analyzed the violence associated with football matches held at the Hawari Abu Madin Stadium in Palestine, due to the continuous cases of violence that appear in this stadium between the teams themselves and the fans. The researcher used the descriptive approach (case study), utilizing the in-depth interviewas well as desk review of some files as study tools. The results of the study showed that sports violence in Hawari Abu Madin Stadium has complex dimensions, including the history of social violence in the Palestinian environment, overlap, status of managing peaceful or confrontational relations between clubs, fanaticism of fans of varying ages and cultures, and the need for adequate Palestinian security forces. In addition, the study pointed out the challenges of controlling the physical environment of the stadium site, entrances, equipment, and preparations. The study recommended a transformative change plan, including a set of activities and a time frame aiming to reach more achievements related to reducing the level of violence. This shall include the need to strengthen ties and relations between all sports institutions as well as develop sensitive programs to educate teams and clubs, including students in schools, about the need to adopt alternatives to violence and confront the behavior of sports violence between students and the public. It was also highlighted that the media should take a more professional role in delivering the bright message of sports that is free from incitement and bias.